2022
DOI: 10.14366/usg.21114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ultrasound point shear wave elastography reliability in an elasticity phantom

Abstract: To date there is a limited number of studies that specifically address the reliability of ultrasound point shear wave elastography (pSWE). Therefore, the aim of the present study was to assess the reproducibility of ultrasound pSWE within and between operators using two ultrasound scanners.Methods: iU22 and EPIQ7 ultrasound scanners were used to assess the reliability of pSWE measurements of lesions at a depth of 3.5 cm in an elasticity phantom using curvilinear 5-1MHz transducer. Intra and inter-operator, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Stiffer tissues exhibit faster shear velocities and higher Young’s moduli. Yuan Shengmei et al 15 performed SWE examinations on mid-pregnancy singleton placentas and found that the placenta elasticity values in the early-onset preeclampsia group were significantly higher than the normal pregnancy group, thereby identifying SWE as useful for evaluating placental function. This study used SWE to assess myometrial elasticity and found that the mean SWE values at the placental attachment site were significantly higher in GDM patients than the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Stiffer tissues exhibit faster shear velocities and higher Young’s moduli. Yuan Shengmei et al 15 performed SWE examinations on mid-pregnancy singleton placentas and found that the placenta elasticity values in the early-onset preeclampsia group were significantly higher than the normal pregnancy group, thereby identifying SWE as useful for evaluating placental function. This study used SWE to assess myometrial elasticity and found that the mean SWE values at the placental attachment site were significantly higher in GDM patients than the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it is known that different factors have been reported to influence the measurements of pSWE. A recent paper published by our group investigated the accuracy and reproducibility of pSWE measured by different operators and ultrasound scanners [28] as factors that could affect pSWE, but not depth. For this reason, in this study, we focused on depth only as a source of variability in pSWE measurements.…”
Section: Discussionmentioning
confidence: 99%